2021
DOI: 10.1021/acschembio.1c00384
|View full text |Cite
|
Sign up to set email alerts
|

Mucinomics as the Next Frontier of Mass Spectrometry

Abstract: Mucin-domain glycoproteins comprise a class of proteins whose densely Oglycosylated mucin domains adopt a secondary structure with unique biophysical and biochemical properties. The canonical family of mucins is well-known to be involved in various diseases, especially cancer. Despite this, very little is known about the site-specific molecular structures and biological activities of mucins, in part because they are extremely challenging to study by mass spectrometry (MS). Here, we summarize recent advancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 182 publications
0
52
0
Order By: Relevance
“…Furthermore, S protein glycosylation is critically involved in human receptor ACE2 binding, 6 cell infectivity, 7 and shields epitopes from antibody neutralization. 8 Although S protein N-glycosylation has been characterized in detail 9 with ongoing efforts to understand the impact of N-glycosylation for vaccine development, 10 characterization of O-glycosylation is challenging 11 due to the large microheterogeneity and structural diversity of O-glycans leading to multiple O-glycoforms. 12 To address these challenges we have recently developed a hybrid top-down mass spectrometry (MS) approach 13 that is capable of simultaneous characterization of the molecular structures, the site specificity, and the relative abundance of various glycoforms along with the overall post-translational modification (PTM) compositions of different coappearing ‘proteoforms’ 14 to enable proteoform-resolved analysis 15 of complex glycoproteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, S protein glycosylation is critically involved in human receptor ACE2 binding, 6 cell infectivity, 7 and shields epitopes from antibody neutralization. 8 Although S protein N-glycosylation has been characterized in detail 9 with ongoing efforts to understand the impact of N-glycosylation for vaccine development, 10 characterization of O-glycosylation is challenging 11 due to the large microheterogeneity and structural diversity of O-glycans leading to multiple O-glycoforms. 12 To address these challenges we have recently developed a hybrid top-down mass spectrometry (MS) approach 13 that is capable of simultaneous characterization of the molecular structures, the site specificity, and the relative abundance of various glycoforms along with the overall post-translational modification (PTM) compositions of different coappearing ‘proteoforms’ 14 to enable proteoform-resolved analysis 15 of complex glycoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the S-RBD is the principal target for neutralizing antibodies and other therapeutics, 4 and that glycosylation plays critical roles in host receptor ACE2 binding and function, [5][6][7][8] it is crucial to decipher the glycoform changes of the Omicron S-RBD as compared to WT and Delta. Although S protein N-glycosylation has been characterized in detail 9,10 with ongoing efforts to understand the impact of N-glycosylation for vaccine development, 11 characterization of O-glycosylation is challenging 12,13 due to the large microheterogeneity and structural diversity of O-glycans leading to multiple O-glycoforms. 14,15 To address these challenges, we have recently developed a hybrid top-down mass spectrometry (MS) approach 16 for comprehensive characterization of O-glycoforms, along with other post-translational modifications (PTMs), to enable proteoform analysis 17,18 of complex glycoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…In N-glycosylation, glycans are attached to Asn when the N-X-S/T consensus motif is present. 11 O-glycans can be attached to any Ser or Thr, regardless of peptide sequence. Mucin domains are regions of dense O-glycosylation with a high content of Pro, Thr, and Ser; within these domains, it is commonly observed that most Ser and Thr residues are modified.…”
Section: Introductionmentioning
confidence: 99%
“…Mucin domains are regions of dense O-glycosylation with a high content of Pro, Thr, and Ser; within these domains, it is commonly observed that most Ser and Thr residues are modified. 11 Various computational approaches can be taken to analyze glycoproteomic data. Many of the commonly used search algorithms, such as SEQUEST, 12 MASCOT, 13 and Andromeda, 14 are able to search glycosylation as a variable modification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation